Distribusi Spasial Total Padatan Tersuspensi Puncak Musim Hujan Di Permukaan Perairan Teluk Benoa, Bali - I Gede Surya Risuana; I Gede Hendrawan; Yulianto Suteja (Journal of Marine and Aquatic Sciences, 2017)
Benoa Bay is semi- enclosed bay, which has embouchures. The existence of embouchures are able to contribute the Total Suspended Solid (TSS) to the Bay. As the one of pollution parameter, TSS could be influencing the ecosystem of coral reefs, seagrass, and the existence of dissolved oxygen. This research was aimed to know the spatial distribution of TSS on the surface layer in Benoa Bay. Sample was taken on January 2016, in flood and ebb. TSS was analyzed using gavimetry method based on SNI No. 06-6989.3-2004. Spatial distribution was analyzed by interpolation method- Inverse Distance Weighted (IDW). The concentration range of TSS on January in ebb to tide and tide to ebb was 22.44 mg/L to 261.33 mg/L. The highest distribution in flood was dominated in around of embouchures. It was suspected by inputs of suspended matter from land to the bay. In tide to ebb condition, TSS concentration was high in some areas, such as around the embouchures, midlle and mouth area of bay. The high concentration was suspected by pattern of tidal current in Benoa Bay. The pattern of current in ebb was leaving to the mouth of Benoa Bay, therefore the TSS concentration dispersed to the mouth of the bay.